ANALISIS TINGKAT KEMAMPUAN TEKNIK SMASH PADA PEMAIN BOLA VOLI PUTRA KLUB MITRA JAYA DESA KOTO TENGAH KECAMATAN KAYU ARO KABUPATEN KERINCI - Ariva Sandi; Jonika Trishandra; Romiya Heliza (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Volleyball is growing very rapidly in villages, especially in Kayu Aro Subdistrict, Kerinci Regency, this is evidenced by the holding of volleyball competitions in each Koto Tengah Village, Kayu Aro Subdistrict, Kerinci Regency competing to foster their athletes to perform optimally in every championship to be the best. As for the development of volleyball in Koto Tengah Village, Kayu Aro Subdistrict, Kerinci Regency, player coaching is carried out in stages from beginner, youth, junior, to senior groups. This is done so that the players who are trained achieve maximum achievement. From the author's observations of several Mitra Jaya players in Kayu Aro District, the problem is during smash training. There are still some players who have poor smash skills, often players in smashing the ball are unable to cross the net, and the ball is not right on target in the volleyball game area or out of the volleyball court. This research is a quantitative descriptive study by looking for a percentage value to determine the analysis of the level of smash technique ability. Data collection techniques are done through tests and measurements. The purpose of this study was to determine the results of the analysis of the level of smash technique ability in volleyball players of Mitra Jaya club, Koto Tengah Village, Kayu Aro District, Kerinci Regency.The results of the assessment of the analysis of the level of ability of smash techniques of volleyball players Putra Club Mitra Jaya Koto Tengah Village, Kayu Aro District, Kerinci Regency are in the good category with a good category of 6 people with a percentage of 46.15%, a very good category of 4 people with a percentage of 30.76%, a fair category of 3 people with a percentage of 23.07%, the results of the assessment of the analysis of the level of ability of smash techniques of volleyball players Putra Club Mitra Jaya Koto Tengah Village, Kayu Aro District, Kerinci Regency are in the good category.